Identification of a carbohydrate recognition domain in filamentous hemagglutinin from Bordetella pertussis. - Prasad, S M (1993)
The adherence of Bordetella pertussis to ciliated cells and macrophages is critical to colonization and infection of the respiratory tract. Adherence to both types of cells involves the recognition of eukaryotic carbohydrates by the bacterial adhesin filamentous hemagglutinin (Fha). The carbohydrate recognition domain (CRD) of Fha is considered an important antigen for subcomponent vaccines to maximize the generation of antiadherence antibodies capable of protecting against colonization. For identification of the CRD of Fha, a bank of eight monoclonal antibodies (MAbs) that mapped to four contiguous regions were tested for their ability to block Fha binding to lactosylceramide or to block bacterial binding to ciliated cells. Only MAb 12.5A9, which maps to amino acid residues 1141 to 1279, blocked both Fha binding to lactosylceramide and bacterial binding to ciliated cells. An 18-kDa polypeptide corresponding to this region was expressed in Escherichia coli. Cell lysates containing this protein bound to lactosylceramide in a manner identical to that of native Fha. Mutant strains of B. pertussis that contained an in-frame deletion of the coding sequence for this region produced a truncated Fha that showed negligible cross-reactivity with MAb 12.5A9. In an adherence assay, these mutant strains failed to bind efficiently to either ciliated cells or macrophages. The numbers of adherent bacteria for these strains were reduced to the number obtained with a nonadherent strain. We conclude that the region defined by residues 1141 to 1279 of Fha constitutes a CRD critical for bacterial adherence and represents a potential candidate for a subcomponent vaccine.